Advances in the development of rare earth metal and carboxylate compounds as corrosion inhibitors for steel. (18th May 2020) - Somers, A. E.; Peng, Y.; Chong, A. L.; Forsyth, M.; MacFarlane, D. R.; Deacon, G. B.; Hughes, A. E.; Hinton, B. R. W.; Mardel, J. I.; Junk, P. C.
ABSTRACT: Research into non-toxic rare earth metal organic compounds providing an alternative to chromates as corrosion inhibitors was pioneered by research at Monash University almost 20 years ago. Further work at Monash and Deakin universities developed lanthanum 4 hydroxy cinnamate, which proved to be as effective as chromate for steel in chloride solution. Recently, attention has turned to substituting the cinnamate anion with 4-methylbenzoyl propanoate. There has also been the development of other non-toxic compounds with the dual functionality of inhibitor and biocide, with a view to combating microbiologically influenced corrosion. A compound 2-methylimidazolinium 4-hydroxycinnamate was synthesised, with corrosion studies showing it to be an effective inhibitor for steel. In this paper, an overview is provided of the recent research in this new area of corrosion inhibition at Deakin and Monash Universities, the mechanisms through which these protective films are thought to form and provide corrosion protection are also discussed. .